2016
DOI: 10.1210/en.2016-1197
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Ligand-Independent Activation of Hippocampal Estrogen Receptor-α by IGF-1 in Hippocampus of Ovariectomized Rats

Abstract: In the absence of ovarian estrogens, increased levels of estrogen receptor (ER)α in the hippocampus are associated with improvements in cognition. In vitro evidence indicates that under conditions of low estrogen, growth factors, including Insulin-Like Growth Factor 1 (IGF-1), can activate ERα and regulate ERα-mediated transcription through mechanisms that likely involve modification of phosphorylation sites on the receptor. The goal of the current work was to investigate a role for IGF-1 in ligand-independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…Growth factors such as insulin-like growth factor-1 (IGF-1) can influence estrogen receptor-dependent transcription in a ligand-independent manner by activating signaling pathways that lead to phosphorylation of estrogen receptors (Smith, 1998). Estrogen receptors and IGF-1 receptors colocalize in cells in the female rodent brain (Cardona-Gómez et al, 2000), and the administration of IGF-1 to the brains of ovariectomized rats results in increased phosphorylation of estrogen receptor α at serine-118 (Grissom and Daniel, 2016). This ligand-independent mechanism is presumed to be independent not only from ovarian estrogens, but from neuroestrogens as well.…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors such as insulin-like growth factor-1 (IGF-1) can influence estrogen receptor-dependent transcription in a ligand-independent manner by activating signaling pathways that lead to phosphorylation of estrogen receptors (Smith, 1998). Estrogen receptors and IGF-1 receptors colocalize in cells in the female rodent brain (Cardona-Gómez et al, 2000), and the administration of IGF-1 to the brains of ovariectomized rats results in increased phosphorylation of estrogen receptor α at serine-118 (Grissom and Daniel, 2016). This ligand-independent mechanism is presumed to be independent not only from ovarian estrogens, but from neuroestrogens as well.…”
Section: Discussionmentioning
confidence: 99%
“…2.1.6 Western Blotting-Western blotting was performed as described previously (Grissom & Daniel 2016) using 15ug of total protein from culture lysate. Separate blots were initially probed for either phospho-T202/Y204 p42/44 ERK (Cell Signaling 9101S; Danvers, MA) or phospho-serine 473 Akt (Cell Signaling 9271S).…”
Section: Sample Collection For Westernmentioning
confidence: 99%
“…We first found that increased levels of ERα in the hippocampus of ovariectomized rats enhances hippocampus-dependent memory (Rodgers et al 2010;Witty et al 2012), through a mechanism dependent on IGF-1R signaling (Witty et al 2013). We have also found that intrahippocampal infusion of IGF-1 increases phosphorylation of ERα at serine-118 and expression of estrogen receptor-dependent target genes (Grissom & Daniel 2016). We have separately shown that continuous, unopposed estradiol exposure enhances hippocampus-dependent memory in ovariectomized rats through a mechanism dependent on brain-derived estradiol (Nelson et al 2016).…”
Section: Introductionmentioning
confidence: 96%
“…Most of these studies indicate cross-talk between peptide growth factor, insulin growth factor and neurotransmitters such as dopamine through kinase activity, not through increasing the level of cyclic nucleotides. 12,[36][37][38] Moreover, it has been documented that cyclic nucleotides promote the phosphorylation of ERα in brain tissues suggesting that cyclic nucleotides are important mediators in the mechanism of estrogen through ERα receptor activity. 38,39 Our present study reports that there was a significant loss in the level of cyclic nucleotides such as cAMP and cGMP in all memory-sensitive brain regions of ovariectomized rodents.…”
Section: Discussionmentioning
confidence: 99%